2022
DOI: 10.7554/elife.78002
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit hyperactivity disorder symptoms and brain morphology: Examining confounding bias

Abstract: Background: Associations between attention-deficit/hyperactivity disorder (ADHD) and brain morphology have been reported, although with several inconsistencies. These may partly stem from confounding bias, which could distort associations and limit generalizability. We examined how associations between brain morphology and ADHD symptoms change with adjustments for potential confounders typically overlooked in the literature (aim 1), and for IQ and head motion, which are typically corrected for but play ambiguo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…We confirm previous reports of global reductions in grey and white matter volume and total surface area in ADHD, as well as widespread regional decreases in CV and SA 5963,65 . We also confirm recent reports of greater, but not lower, CT, which contradict some earlier studies of ADHD 6064,72,73 . Of note, head motion poses a critical challenge in neuroimaging studies of ADHD 72 (as well as autism 113,147 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We confirm previous reports of global reductions in grey and white matter volume and total surface area in ADHD, as well as widespread regional decreases in CV and SA 5963,65 . We also confirm recent reports of greater, but not lower, CT, which contradict some earlier studies of ADHD 6064,72,73 . Of note, head motion poses a critical challenge in neuroimaging studies of ADHD 72 (as well as autism 113,147 ).…”
Section: Discussionsupporting
confidence: 88%
“…We also confirm recent reports of greater, but not lower, CT, which contradict some earlier studies of ADHD 6064,72,73 . Of note, head motion poses a critical challenge in neuroimaging studies of ADHD 72 (as well as autism 113,147 ). Thus, it is possible that earlier reports of cortical thinning in ADHD were confounded by motion and other aspects of MRI quality 148 , along with small sample sizes, as has been observed in autism 112,113 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, we found that the association between ADHD symptoms and the surface area of the middle temporal gyrus, as well as the thickness of the fusiform gyrus, were stronger after weighting. Previous attempts in population studies did not found significant associations of thickness measures with ADHD symptoms (Dall'Aglio et al, 2022), while other studies do find these associations with ADHD (Shaw et al, 2007). Selection bias could potentially be a part of the explanation for this discrepancy.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous neuroimaging studies have been conducted to examine possible structural brain alterations associated with ADHD; however, many of their findings have been inconsistent or even contradictory (Samea et al, 2019). While several explanations exist for these inconsistencies, various forms of bias have been proposed as a possible explanation for these inconsistent results, indeed adjusting for a more comprehensive set of confounding factors altered some associations between brain structure and ADHD symptoms (Dall'Aglio et al, 2022). Next to confounding bias, selection bias (e.g., self‐selection into a study or loss to follow‐up) is another possible source of bias that could alter the interpretation of results.…”
Section: Introductionmentioning
confidence: 99%